Randomization in randomized clinical trials: From theory to practice - Mina Mohammady; Leila Janani (Tehran University of Medical Sciences, 2016)
Background & Aim: Randomized clinical trials (RCTs) are studies which are able to provide the most valid evidence to compare various interventions in health research. Biases can affect the quality of research and ultimately make the results of a study invalid. One of the most important biases is selection bias. The best way to reduce selection bias is the use of random allocation. The aim of this study is to provide comprehensive, practical and simple information regarding proper implementation of the random allocation process in randomized clinical trials. Methods & Materials: A review study was performed using available resources and comprehensive analysis. For this purpose, we searched the relevant books & articles in databases including Medline, Scopus, Science Direct, Google Scholar and Magiran. Key words were randomization, random sequence, allocation concealment, randomized controlled trial, randomized clinical trial, and bias. Results: From the literature review, we obtained 39 articles and one relevant book that their findings were presented in a simple language with practical examples in three parts including random sequences generation, random allocation concealment and implementation. Conclusion: Selection bias in clinical trials has an adverse effect on the accuracy of results. In order to avoid it, researchers should employ proper methods in randomization and random allocation concealment, and report it in their articles properly. Therefore, researchers can obtain valid results through a better understanding of randomization and its proper implementation.